Efficacy, safety, and tolerability of lacosamide monotherapy versus controlled-release carbamazepine in patients with newly diagnosed epilepsy: a phase 3, randomised, double-blind, non-inferiority trial. Issue 1 (January 2017) - Baulac, Michel; Rosenow, Felix; Toledo, Manuel; Terada, Kiyohito; Li, Ting; De Backer, Marc; Werhahn, Konrad J; Brock, Melissa
Summary: Background: Further options for monotherapy are needed to treat newly diagnosed epilepsy in adults. We assessed the efficacy, safety, and tolerability of lacosamide as a first-line monotherapy option for these patients. Methods: In this phase 3, randomised, double-blind, non-inferiority trial, patients from 185 epilepsy or general neurology centres in Europe, North America, and the Asia Pacific region, aged 16 years or older and with newly diagnosed epilepsy were randomly assigned in a 1:1 ratio, via a computer-generated code, to receive lacosamide monotherapy or controlled-release carbamazepine (carbamazepine-CR) twice daily. Patients, investigators, and trial personnel were masked to treatment allocation. From starting doses of 100 mg/day lacosamide or 200 mg/day carbamazepine-CR, uptitration to the first target level of 200 mg/day and 400 mg/day, respectively, took place over 2 weeks. After a 1-week stabilisation period, patients entered a 6-month assessment period. If a seizure occurred, the dose was titrated to the next target level (400 or 600 mg/day for lacosamide and 800 or 1200 mg/day for carbamazepine-CR) over 2 weeks with a 1-week stabilisation period, and the 6-month assessment period began again. Patients who completed 6 months of treatment and remained seizure-free entered a 6-month maintenance period on the same dose. The primary efficacy outcome was the proportion of patients remaining free from seizures for 6 consecutive months after stabilisation at the last assessed dose. The predefined non-inferiority criteria were −12% absolute and −20% relative difference between treatment groups. This trial is registered withClinicalTrials.gov, numberNCT01243177 . Findings: The trial was done between April 27, 2011, and Aug 7, 2015. 888 patients were randomly assigned treatment. 444 patients taking lacosamide and 442 taking carbamazepine-CR were included in the full analysis set (took at least one dose of study treatment), and 408 and 397, respectively, were included in the per-protocol set. In the full analysis set, 327 (74%) patients in the lacosamide group and 308 (70%) in the carbamazepine-CR group completed 6 months of treatment without seizures. The proportion of patients in the full analysis set predicted by the Kaplan-Meier method to be seizure-free at 6 months was 90% taking lacosamide and 91% taking carbamazepine-CR (absolute treatment-difference: −1·3%, 95% CI −5·5 to 2·8 relative treatment difference: −6·0%). Kaplan-Meier estimates results were similar in the per-protocol set (92% and 93%; −1·3%, −5·3 to 2·7; −5·7%). Treatment-emergent adverse events were reported in 328 (74%) patients receiving lacosamide and 332 (75%) receiving carbamazepine-CR. 32 (7%) patients taking lacosamide and 43 (10%) taking carbamazepine-CR had serious treatment-emergent adverse events, and 47 (11%) and 69 (16%), respectively, had treatment-emergent adverse events that led to withdrawal. Interpretation: Treatment with lacosamide met the predefined non-inferiority criteria when compared with carbamazepine-CR. Therefore, it might be useful as first-line monotherapy for adults with newly diagnosed epilepsy. Funding: UCB Pharma.